Can obesity and physical activity predict outcomes of elective knee or hip surgery due to osteoarthritis? A meta-analysis of cohort studies - Pozzobon, Daniel (2018)
The aim of this study was to systematically review the literature to identify whether obesity or the regular practice of physical activity are predictors of clinical outcomes in patients undergoing elective hip and knee arthroplasty due to osteoarthritis. Design Systematic review and meta-analysis. Data source and eligibility criteria A systematic search was performed on the Medline, CINAHL, EMBASE and Web of Science electronic databases. Longitudinal cohort studies were included in the review. To be included, studies needed to have assessed the association between obesity or physical activity participation measured at baseline and clinical outcomes (ie, pain, disability and adverse events) following hip or knee arthroplasty. Data extraction Two independent reviewers extracted data on pain, disability, quality of life, obesity, physical activity and any postsurgical complications. Results 62 full papers were included in this systematic review. From these, 31 were included in the meta-analyses. Our meta-analysis showed that compared to obese participants, non-obese participants report less pain at both short term (standardised mean difference (SMD) 0.43; 95% CI 0.67 to 0.19; P<0.001) and long term post-surgery (SMD 0.36; 95% CI 0.47 to 0.24; P<0.001), as well as less disability at long term post-surgery (SMD 0.32; 95% CI 0.36 to 0.28; P<0.001). They also report fewer postsurgical complications at short term (OR 0.48; 95% CI 0.25 to 0.91; P<0.001) and long term (OR 0.55; 95% CI 0.41 to 0.74; P<0.001) along with less postsurgical infections after hip arthroplasty (OR 0.33; 95% CI 0.18 to 0.59; P<0.001), and knee arthroplasty (OR 0.42; 95% CI 0.23 to 0.78; P=0.006). Conclusions Presurgical obesity is associated with worse clinical outcomes of hip or knee arthroplasty in terms of pain, disability and complications in patients with osteoarthritis. No impact of physical activity participation has been observed. PROSPERO registration number CRD42016032711.